(untitled) (Revista de História da UEG (REVHIST), 2023)
The mythological discourse had an important influence on the Athenian Democracy, as well as the division of female and male roles. Thus, in this article we decided to present the role of the wives of the Athenian citizen (also known as Mélissa or Gynaikes) and their relationship with the founding myth of Athens. In this perspective, they emerge through new horizons in which their participation has become essential for the civic and political community. In this sense, Pericles’ law that made citizens only children of Athenian mothers and fathers, allowed them, even if indirectly, an indirect participation in politics. Keywords: Myth. Wife. Politics. Women.